Selectivity Modeling Analysis of Natural Gas Binary Components via Adsorption on 5A Zeolites - Eissa, Eissa Mubarak (IRC, 2016)
The increased demand for more energy which is cost effective and eco friendlier opens the opportunity for more studies that concerns of CO2 removal from the natural gas, due to the lack of studies regarding binary mixture, the ideal adsorbed solution (IAS) theory and Extended Langmuir models have been studied for predicting multicomponent adsorption equilibria from isotherms for single gases in order to develop and validate the applicability of models to predict the selectivity of CO2/CH4 separation using 5A zeolite in 500C and 700C and pressure of 10 bar. For this projects, single component mixture and binary component mixture have been analyzed, for single component mixture there are six isotherm models utilized and 5A zeolite has high tendency to adsorb CO2 more than CH4 and the adsorption behaved as monolayer behavior which agreed with Langmuir model, toth and sips isotherm models approved that the adsorption is heterogeneous(non-homogeneous).